Designing Green Space for Improving the Quality of Streetscape of Rungkut Madya Surabaya - Heru Prasetiyo Utomo; Wiwik Dwi Susanti; Fairuz Mutia (Future Science)
Today, urban planning cannot be carried out without considering the ecological balance. Rungkut Madya Street, is a fairly dense secondary arterial road in the city of Surabaya which indirectly contributes to high pollution. The lack of trees and also a low assessment of aesthetic values have resulted in many environmental problems such as dust, heat and noise that must be faced by the community on Jalan Rungkut Madya. The construction of the MERR road and the OERR road plan by the Surabaya City Government and the East Java Provincial Government indirectly influence the existence of green space due to the high economic value of the land so that it becomes a strong impetus for the conversion of land into buildings. To solve this case, the research method used qualitative exploratory and descriptive which is focused on describing the authenticity of the shape and character of green space in the corridor of Rungkut Madya Street through the Character Appraisal Research analysis technique. Data collection is carried out by observation directly in the field to explain the reality and potential that exists. Then arranged in a mapping based on scientific studies. Next is to identify and analyze the potential and problems of the region to find a description of the criteria and concepts, followed by the preparation of a schematic model of the arrangement of green open space in the corridor of the Rungkut Madya Surabaya road. The research aims to produced a good quality green space design for improving the quality of the streetscape.